Pengembangan Aplikasi Pemesanan Lapangan Futsal Di Kota Malang Berbasis Android Menggunakan Metode Pengembangan Extreme Programming (Studi Kasus Champion Tidar, Zona SM Futsal, dan Viva Futsal) - Artiyan Prasetya; Adam Hendra Brata; Mahardeka Tri Ananta (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Futsal is the one of the sport that is growing in indonesia, especially in the city of malang. The development of futsal in Malang has some parties who exploit these conditions to make it land business, such as futsal field provides for renting service. Many field provider do not provide information or convenience in reservating such a field. According to the results of a survey the Association's Internet Service Provider Indonesia (APJII) in the year 2016, 47.6% or 63.1 million Indonesian people accessing the internet through their mobile devices. Based on condition, in order to help information deliver and help give the ease of reserve a field, the field reservating application implemented on an android mobile device. This application was developed using the method of development of Extreme Programming which is the simplest method in the process of designing and coding, so that it can reduce amount of development time. In addition, this method is suitable for dealing with the needs of users which didn't clear and easy to change. Based on the test results obtained by the use of usability methods SUS, application of malang futsal field reservations get assessment from eight user with the value of an average score on user side is 77 and the officer side is 73.3. Then from the results it can be concluded that the application is declared acceptable, so that's mean this applications can be declared as acceptable and easy to used by the user.